2013
DOI: 10.1016/j.ijid.2012.05.1033
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whipplei prevalence strongly suggests human transmission in homeless shelters

Abstract: Tropheryma whipplei prevalence strongly suggests human transmission in homeless sheltersThe spectrum of infections due to Tropheryma whipplei is wide. [1][2][3] The bacterium is detected with variable prevalence in stool and saliva specimens from healthy individuals. [4][5][6] In France, the prevalence of T. whipplei in stool samples from the general adult population is estimated to be approximately 3%. 4 We report the prevalence of T. whipplei carriage in stool and saliva specimens from homeless people living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…Several findings support the theory of inter-human transmission of T. whipplei, 14 including the existence of specific T. whipplei clones, not only among the population of Dielmo and Ndiop 10 but also among children during episodes of T. whipplei gastroenteritis, 4 among relatives of people positive for T. whipplei, 12 and among homeless people sleeping in the same shelter. Having analyzed the questionnaires, the only factor significantly associated with the circulation of T. whipplei within households is a lack of toilets in households.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Several findings support the theory of inter-human transmission of T. whipplei, 14 including the existence of specific T. whipplei clones, not only among the population of Dielmo and Ndiop 10 but also among children during episodes of T. whipplei gastroenteritis, 4 among relatives of people positive for T. whipplei, 12 and among homeless people sleeping in the same shelter. Having analyzed the questionnaires, the only factor significantly associated with the circulation of T. whipplei within households is a lack of toilets in households.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, the relationship of the lack of toilet facilities to the detection of T. whipplei in households supports the theory of human-to-human transmission of the bacterium, with the inter-human transmission being from human feces through hand transmission. 14 Tropheryma whipplei is known to be viable in human fecal and saliva samples, suggesting that the bacterium might be transmitted through both fecal-oral and oro-oral routes. 26,27 Depending on the living conditions of the subjects, either method of transmission may be prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity of the T. whipplei genome was subsequently confirmed by a study of 34 children with gastroenteritis in Marseille, France, as 12 new genotypes were detected (15). While there were many distinct genotypes observed, infections with type 1 and 3 are predominant, as they account for 35% of all European samples and caused small clonal outbreaks in central Europe (15,54,99). In a recent study, 72 different genotypes of T. whipplei have been found among strains from 191 positive samples from patients from central Europe (99).…”
Section: Bacterial Factorsmentioning
confidence: 86%
“…Also, in a study in Senegal, only three different epidemic genotypes were found (17). Finally, outbreaks of two different genotypes in homeless shelters in France have been reported (54). These three studies all suggest that clonal outbreaks of T. whipplei do occur.…”
Section: Human Carriage and Human-to-human Transmissionmentioning
confidence: 91%